Impact of Litter Quality and Earthworm Populations on Seruk Spring Forest’s Soil Characteristic - Abban Putri Fiqa; Siti Sofiah (Jurnal Penelitian Hutan dan Konservasi Alam, 2021)
Seruk spring, located in Batu, East Java, is a spring with four different Land Use Systems (LUS) in its surrounding area, comprising a mixed, a pine, an eucalypt, and a bamboo forests. Over time, there have been changes in land use around the area of Seruk Spring. This results in a decrease in the environmental quality, and even in the spring’s water discharge. As spring serves as an important part of people living in the immediate vicinity, this research aimed to determine the differences in litter quality, earthworm populations, and soil porosity at each LUS. Litter was measured in each area and analyzed in the laboratory to determine its biomass and quality. Earthworm populations and biomass were measured with the iron box method, while the soil porosity and organic matter were based on secondary data from the previous research. The correlation among all the parameters was analyzed with Principal Components Analysis (PCA) using PAST 3 software. The results showed that the bamboo forest had the most suitable land-use system around spring, based on the highest litter thickness and its quality in the area. The different qualities of each LUS provided diverse advantages for the spring ecosystem. The presence of the bamboo forest around the spring area should be conserved, to maintain the quality of the ecosystem and the sustainability of the spring area itself.